An intelligent approach to design three-dimensional aircraft sheet metal part model for manufacture - Tan, Hao; Liu, Chuang; Chen, Hui; Wang, Junbiao (Cranfield University Press, 2013)
Aircraft sheet metal part manufacturing is a knowledge-intensive process, and the manufacturability and manufacturing information are required to be considered in three-dimensional (3D) model by knowledge reuse. This paper presents a 3D model structure of the aircraft sheet metal part and an intelligent approach to design the model for manufacture combining intelligent manufacturability analysis with manufacturing information definition. Processability of part, formability of material and cost of fabrication are proposed to analyse the manufacturability of the part. Knowledge base for manufacturability analysis is established, and knowledge is reused to evaluate the part’s manufacturability intelligently to meet the constraints of manufacturing conditions. Non-geometric information is defined in the 3D model to meet the needs of digital manufacturing and inspection using model-based technology. An example is given to describe the process of design for manufacture, which shows that the approach can realize the concurrent design and digital manufacturing of aircraft sheet metal.
Keywords: design for manufacture; intelligent manufacturability analysis; knowledge reuse